Patterns of alcohol dependence in Thai drinkers: A differential item functioning analysis of gender and age bias - Srisurapanont M. (2014)
In Caucasians, the patterns of alcohol use disorders in women and adolescents are likely to be different from those in men and adults, respectively. The authors examined these differences in a Southeast Asian sample of Thai people living in communities. A two-parameter logistic model of the IRT log-likelihood-ratio (IRTLR) test for differential item functioning (DIF) procedure was used. Participants were a subsample of 3718 current drinkers participating in the 2008 Thai National Mental Health Survey (n = 17,140). The 1-year prevalence rates of alcohol dependence were 1.4% in women and 13.7% in men. Based on the Mini International Neuropsychiatric Interview (MINI), alcohol dependence and abuse module, all current drinkers were interviewed for a yes/no response to each of seven alcohol dependence criteria. Confirmatory factor analysis suggested a single-factor model of alcohol dependence criteria (χ2 = 211.51, RMSEA = 0.06, SRMR = 0.03 and CFI = 0.96). Compared with 3174 men, 544 women had a significantly higher threshold estimate for quit/control problems and a lower threshold value for drinking despite physical/mental problems (b parameter difference of 0.25 and - 0.30, respectively). Thai adolescents (n = 272) and Thai adults (n = 3446) had no statistically significant DIF on any criterion. The criterion of time spent drinking had significantly high discrimination estimates in women, men, adolescent and adults (a parameters of 2.50, 2.08, 2.33 and 2.16, respectively). Gender bias on alcohol dependence criteria can be found in Thai drinkers. Time spent drinking may be the most useful criterion for discriminating the severity of alcohol dependence across age and gender groups of Thai drinkers. © 2011 Elsevier Ltd.